EVALUATION OF SPORTS EDUCATION AND SOCIAL INCLUSION - PARTHASARATHY, S.; DHANARAJ, S. (International Journal of Psychosocial Rehabilitation, 2020)
The Concept of this study evaluation of sports education and social inclusion of new education policy. That can made few singularity of old education. It was finalized that the sports education can made the great contributions towards the promotion of the current society.